2004
DOI: 10.1016/j.ejphar.2004.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of trimetazidine on myocardial mitochondrial function in an ex-vivo model of global myocardial ischemia

Abstract: Trimetazidine is an anti-ischemic drug whose cytoprotective mechanisms are not yet fully understood (but until now mainly related to the trimetazidine-induced bmetabolic shiftQ from lipid h-oxidation to glucose aerobic oxidation). We studied the effect of trimetazidine on the mitochondrial function of ischemic Wistar rat hearts perfused with glucose, using a model of ex-vivo perfusion (Langendorff system). We measured the electrical potential of the mitochondrial membrane, O 2 consumption by the respiratory ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 16 publications
3
20
0
Order By: Relevance
“…Other reports showed that ANG II inhibition improved cardiac mitochondria energy production (289,290,307), and in diabetic rats captopril treatment upregulated the expression of genes related to energy production (74). Among the potential factor(s) that may mediate the effects of ANG II inhibitors on mitochondrial function, mitochondrial NO was suggested to contribute to the renal mitochondrial actions of enalapril (317), and ARBs were found to modulate UCP mRNA levels in mouse brown adipose tissue (12) and rat liver (78), or UCP protein content in rat kidney (103,317).…”
Section: Ras-bl and Agingmentioning
confidence: 99%
“…Other reports showed that ANG II inhibition improved cardiac mitochondria energy production (289,290,307), and in diabetic rats captopril treatment upregulated the expression of genes related to energy production (74). Among the potential factor(s) that may mediate the effects of ANG II inhibitors on mitochondrial function, mitochondrial NO was suggested to contribute to the renal mitochondrial actions of enalapril (317), and ARBs were found to modulate UCP mRNA levels in mouse brown adipose tissue (12) and rat liver (78), or UCP protein content in rat kidney (103,317).…”
Section: Ras-bl and Agingmentioning
confidence: 99%
“…The precise mechanism by which trimetazidine partially inhibits FAO remains controversial; some investigators advocate a selective inhibition of long-chain 3-ketoacyl CoA thiolase, 139 whereas other investigators reject this. 140 Trimetazidine has additional effects, 141 such as mitochondrial protection, 142 lessened proton production, 143 and endothelial protection. 144 Thus, although trimetazidine has in part delivered on the promise of metabolic modulation in human HF (Table 3), 138,[145][146][147][148][149][150][151][152][153][154][155] it is unlikely to be marketed for HF because of patent issues.…”
Section: Decrease Of Fatty Acid Metabolism By Fatty Acid Oxidation Inmentioning
confidence: 99%
“…Under ischemic conditions, TMZ is known to improve mitochondrial metabolism by decreasing oxygen consumption (Monteiro et al, 2004). To check whether TMZ treatment affected oxygen consumption by MSCs under the given experimental conditions, we determined the OCR of the cells using EPR oximetry.…”
Section: Effect Of Hypoxia and H 2 O 2 On The Viability Of Mscsmentioning
confidence: 99%